Stuck in translation: Stakeholder perspectives on impediments to responsible digital health - Landers, Constantin; Vayena, Effy; Amann, Julia; Blasimme, Alessandro (Frontiers in Digital Health, 2023)
Digital health promises to profoundly transform medicine. At the same time, however, it raises conspicuous ethical and regulatory issues. This has led to a growing number of calls for responsible digital health innovation. Based on stakeholder engagement methods, this paper sets out to identify core impediments hindering responsible digital health. We developed a participatory research methodology to access stakeholders’ fragmented knowledge of digital health, engaging 46 digital health stakeholders over a period of five months (December 2020 – April 2021). We identified ineffective stakeholder collaboration, lack of ethical awareness among digital health ’s innovators, as well as lack of relevant regulation, as core impediments to responsible digital health. The stakeholders’ accounts indicate that ethical concerns may considerably slow the pace of digital health innovation – implying that responsible innovation is a core catalyst for the progress of digital health overall.